Public Administration of Thailand under the Welfare State system - Woraphatthirakun, Paphassorn (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
This article aims to introduce the concepts and Principles of welfare state administration by using the success of Sweden as a major case study. The results showed that Thailand’s welfare system is still far from it’s goal, no matter how the Thai government has been trying the best of its efforts to turn Thailand into a desirable welfare state trough various promoting policies. This article strongly suggested that the welfare state principles be implemented and Henry Fayol’s “the principles of management, POCCC” be applied to effectively and efficiently eliminate financial and social inequality of Thai people. Even if the government has to confront with obstacles and problems inevitably. Article history : Accepted 4 May 2017 SIMILARITY INDEX = 1.24